2022
DOI: 10.3390/jcm11113069
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity and Associated Comorbidities on the Outcomes after Renal Transplantation with a Living Donor vs. Deceased Donor Grafts

Abstract: Background: Obesity among kidney transplant (KT) recipients can lead to metabolic comorbidity-associated deaths. This study compares post-KT survival between obese and non-obese patients and outcomes of living donor (LD) and deceased donor (DD) grafts. Methods: Between January 2005–May 2019, 1403 KT recipients from a single center were included in the study, as well as 314 patients (22.4%) with obesity (BMI > 30 kg/m2), 137 DD transplants, and 177 LD transplants. Of the 1089 (77.6%) in the control group (BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Obesity among KTx recipients and its association with graft outcomes was another area of study. Obesity was associated with decreased graft survival, more DGF, increased postoperative surgical complications, [24][25][26] longer procedure duration, and longer warm ischemia time. 27 Tsapepas et al found that body mass index (BMI) ≥35 was associated with increased surgical site infections on multivariable analysis (adjusted OR 3.34; 95% CI 1.55-7.22; P = .022), though this study did not find the increased rate of graft failure in obese patients that was found in prior studies.…”
Section: Obesitymentioning
confidence: 95%
“…Obesity among KTx recipients and its association with graft outcomes was another area of study. Obesity was associated with decreased graft survival, more DGF, increased postoperative surgical complications, [24][25][26] longer procedure duration, and longer warm ischemia time. 27 Tsapepas et al found that body mass index (BMI) ≥35 was associated with increased surgical site infections on multivariable analysis (adjusted OR 3.34; 95% CI 1.55-7.22; P = .022), though this study did not find the increased rate of graft failure in obese patients that was found in prior studies.…”
Section: Obesitymentioning
confidence: 95%
“…Obesity is associated with increased risk for delayed graft function (DGF), defined as the need for dialysis within 7 days after transplantation but the underlying cause for this remains unclear [13,14 ▪ ,15–18,19 ▪ ,25–29]. Although obesity is associated with a proinflammatory environment with elevated levels of cytokines and chemokines, technical challenges encountered in performing the transplantation may lead to a longer warm ischemic time and other anatomical challenges.…”
Section: Delayed Graft Functionmentioning
confidence: 99%
“…It is conceivable that this is because of improvement in general posttransplant care including advances in immunosuppressive therapy. A recent single-center study reported that recipients with a BMI greater than 30 kg/m 2 had higher risk of both graft and patient loss at 1, 5, and 10 years after transplantation compared wth control group (BMI ≤30 kg/m 2 ) [28]. This is in contrast to the retrospective study by Jarv that reported that obesity (BMI ≥25 kg/m 2 ) was associated with worse short-term (5-year) graft (BMI <25 versus ≥25 kg/m 2 , 67 versus 61%, P < 0.05) and patient survival (BMI <25 versus ≥25 kg/m 2 , 80 versus 70%, P < 0.05), but no statistically significant difference in long-term (10-year) graft survival, and only minimal difference in long-term patient survival [36].…”
Section: Graft and Patient Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence has nearly tripled over the last 50 years due to less healthy diets and progressively more sedentary lifestyles 1. At present, more than one-third of the world’s population meet the criteria for obesity 2. It is associated with increased morbidity and mortality, exacerbating underlying conditions such as heart disease, renal disease and liver disease, which, in turn, can lead to end-stage organ disease 3.…”
Section: Introductionmentioning
confidence: 99%